Performance Measurement of a Construction Consulting Company Using Integrated Performance Prism and Fuzzy Analytical Hierarchy Process (Fuzzy AHP) - Arfandi ahmad; muhammad Dahlan (Journal of Industrial System Engineering and Management, 2025)
Performance measurement plays a strategic role in translating a company's strategy into concrete action and in evaluating the achievement of organizational goals, particularly for consulting service firms whose performance depends heavily on the satisfaction of multiple stakeholders. PT. Galaksi Prima Consultant, a construction consulting company in Makassar, has not implemented a performance measurement system that comprehensively accommodates the interests of its customers, employees, owner, and suppliers, so that its overall performance has not been systematically monitored. This study develops a performance measurement model that integrates the Performance Prism framework to identify Key Performance Indicators (KPIs) from five perspectives, with the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) to determine the weight of importance of each KPI while accommodating the uncertainty of expert judgment. Pairwise comparison results were converted into Triangular Fuzzy Numbers and processed through fuzzy synthesis and defuzzification to obtain crisp weights, all of which passed the consistency test (CR < 0.1). The results show that 55 KPIs were identified across four stakeholder groups, with the customer perspective obtaining the highest weight (0.374), followed by employees (0.289), suppliers (0.230), and owner (0.107). The overall performance score of PT. Galaksi Prima Consultant was 2.919, which falls into the moderate/fairly good category. The proposed model provides a systematic and replicable reference for measuring and improving the performance of construction consulting companies..